2014
DOI: 10.1002/ana.24093
|View full text |Cite
|
Sign up to set email alerts
|

Sex Is a major determinant of neuronal dysfunction in neurofibromatosis type 1

Abstract: Objective Children with Neurofibromatosis-1 (NF1) are at risk for developing numerous nervous system abnormalities, including cognitive problems and brain tumors (optic pathway glioma). Currently, there are few prognostic factors that predict clinical manifestations or outcomes in patients, even in families with an identical NF1 gene mutation. In this study, we leveraged Nf1 genetically-engineered mice (GEM) to define the potential role of sex as a clinically-relevant modifier of NF1-associated neuronal dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 33 publications
7
96
1
3
Order By: Relevance
“…Our study also found an increased risk for need for therapy in females with NF1 and OPG, confirming recent studies suggesting that sex plays a role in the development of gliomas and neuronal dysfunction in patients with NF1. 21,22 A recent large multicenter study of visual outcomes in children with NF1 and OPG showed that at completion of chemotherapy, visual acuity improved in 32% of subjects, remained stable in 40%, and declined in 28%. 23 There are a number of limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found an increased risk for need for therapy in females with NF1 and OPG, confirming recent studies suggesting that sex plays a role in the development of gliomas and neuronal dysfunction in patients with NF1. 21,22 A recent large multicenter study of visual outcomes in children with NF1 and OPG showed that at completion of chemotherapy, visual acuity improved in 32% of subjects, remained stable in 40%, and declined in 28%. 23 There are a number of limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, multiple studies have suggested a role of sex on the severity of defects in individuals with RASopathies. For example, studies of RASopathy mouse models associated with Neurofibromatosis 1 (NF1) showed that females have more severe neuronal dysfunction than males (44).…”
Section: Resultsmentioning
confidence: 99%
“…In Nf1 optic glioma mice, reduced cAMP levels and higher levels of RGC apoptosis are observed in females, leading to reduced visual acuity in female mice only. 53 Moreover, while the frequency of OPG development is similar in girls and boys with NF1, 3 times more females with NF1-OPG require treatment for visual decline. 53 These findings support a role for sex as a critical factor that underlies clinical outcomes in children with NF1-OPG.…”
Section: Use Of Nf1 Gem Strains To Understandmentioning
confidence: 99%
“…As mentioned above, female mice as well as female humans with NF1-OPG are more likely to experience visual decline and require treatment than their male counterparts. 53 These observations raise the possibility that females have different epigenetic programming due to X-chromosome influences, which change the intracellular context in which changes in neurofibromin expression affect biological outcomes. Identifying these epigenetic determinants may reveal new genes for risk stratification and therapeutic targeting.…”
Section: Translating Basic Science Discoveries Tomentioning
confidence: 99%
See 1 more Smart Citation